Het Museum. (Turnhout : De Warande, 1993)
Maes, Karel ; Vaerten, Jan ; Cornelissen, Remy ; Dries, Jan ; Van Pelt, Wim ; Selen, Max ; Minnen, Hugo ; Geys, Jef ; Van Grieken, Jef ; Van Gestel, Fik ; Luyten, Marc ; Van Soom, Luk ; Vandevelde, Ludwig ; etc.
Het Museum, De Warande, Turnhout, van 26 juni tot en met 5 september 1993
Nederlands
kunstcatalogus